Physiological and transcriptomic study reveal SeNPs-mediated AsIII stress detoxification mechanisms involved modulation of antioxidants, metal transporters, and transcription factors in Glycine max L. (Merr.) roots. (15th January 2023) - Zeeshan, Muhammad; Hu, Yu Xin; Guo, Xiao Hong; Sun, Chen Yu; Salam, Abdul; Ahmad, Shakeel; Muhammad, Ihsan; Nasar, Jamal; Jahan, Mohammad Shah; Fahad, Shah; Zhou, Xun Bo
Abstract: Physiological changes and genome-wide alteration in gene expression were performed in soybean (Glycine max [L.] Merr.) roots exposed to AsⅢ (25 μmol/L) alone and supplemented with selenium nanoparticles (SeNPs) at the concentration of 10 and 25 μmol/L at the V2 growth stage. Excessive arsenic in the root zone poses a potential threat to soybean yield, particularly to roots, due to the limited translocation of AsIII from root to shoot in the case of soybean. We hypothesized that SeNPs can relieve AsⅢ toxicity to soybean root by reducing the AsⅢ uptake and regulating the internal tolerance mechanism of the plants. Results accomplished that SeNPs had positive impact on soybean dry weight and roots parameters under AsⅢ stress. Then, we further evaluated physiological indexes, whole genome transcriptomic analysis and quantitative real-time PCR to elucidate the underlying mechanism of AsⅢ tolerance under SeNPs supplementation. Under the condition of AsⅢ-stress, SeNPs exposure significantly reduced the electrolyte leakage, O2 −, H2 O2 and MDA accumulation while increasing the antioxidants level. The RNA-seq dataset revealed total of 5819 up and 7231 down expressed DEGs across all libraries. The number of exclusively regulated genes were higher under As + SeNP10 (4909) treatment than in the AsⅢ-alone (4830) and As + SeNP25 (3311) treatments. The KEGG and GO analyses revealed that stress responsive DEGs such as glutathione S-transferase, glutathione peroxidase, ascorbate, glutaredoxin, thioredoxin, and phytochelatins synthase are responsible for AsⅢ tolerance under the SeNPs supplementation. Similarly, sulfate transporter, and ABC transporters (ATP-binding cassettes) expression were induced, and aquaporin channels related DEGs expression were reduced under SeNPs application in AsⅢ exposure condition. Furthermore, the expression of molecular chaperones (HSP) and transcription factors (MYB, bZIP, bHLH, and HSFs) were increased in SeNPs treatment groups. These results provide vital information of AsⅢ tolerance mechanism in response to SeNPs in soybean. We suggest that functional characterization of these genes will help us learn more about the SeNPs responsive arsenic tolerance mechanism in soybean. Highlights: The impact of SeNPs on AsIII stress mitigation were assessed. SeNPs relieved ion leakage and protected the bio-mambrane lipids against oxidative stress. SeNPs induced expression of molecular chaperones (HSP) and transcription factors under AsIII treatment.